2019
DOI: 10.1002/jso.25632
|View full text |Cite
|
Sign up to set email alerts
|

Race, ethnicity, and socioeconomic factors in cholangiocarcinoma: What is driving disparities in receipt of treatment?

Abstract: Background and Objectives: Race/ethnicity and socioeconomic factors are associated with worse cancer outcomes. Our aim was to determine the association of these factors with receipt of surgery and multimodality therapy for cholangiocarcinoma.Methods: Patients with cholangiocarcincoma in the National Cancer Database were identified. Racial/ethnic groups were defined as non-Hispanic White, non-Hispanic Black, Asian, and Hispanic. Socioeconomic factors were insurance status, income, and education.Results: Of 12 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…Ha et al [ 25 ] suggested that blacks and Hispanics were less likely to receive curative therapy for HCC due to the advanced stage at presentation of HCC. Similar observations in racial and socioeconomic disparities were found in Hispanic patients with CC[ 26 , 27 ]. While all of these observations suggest a worse outcome for Hispanics with HCC or CC, ours is the first to describe a non-inferior prognosis for Hispanics with the combined HCC/CC variant.…”
Section: Discussionsupporting
confidence: 78%
“…Ha et al [ 25 ] suggested that blacks and Hispanics were less likely to receive curative therapy for HCC due to the advanced stage at presentation of HCC. Similar observations in racial and socioeconomic disparities were found in Hispanic patients with CC[ 26 , 27 ]. While all of these observations suggest a worse outcome for Hispanics with HCC or CC, ours is the first to describe a non-inferior prognosis for Hispanics with the combined HCC/CC variant.…”
Section: Discussionsupporting
confidence: 78%
“…rural location, and Medicaid or lack of health insurance have been linked to disparities in treatment and outcomes for complex gastrointestinal malignancies. [10][11][12][13][14] Socioeconomic status (SES), commonly derived from census-level data, has been highlighted as a common factor that may underlie these barriers to treatment. 15 With regard to colorectal cancer, SES has been correlated with advanced stage at presentation, delays in care, less minimally invasive surgery, and inferior survival.…”
mentioning
confidence: 99%
“…Disparities in cancer outcomes arising from lack of access to safe, timely, and affordable care are associated with delays in care, increased morbidity, and higher mortality rates 1‐4 . Geographical access and the ability to navigate the complex healthcare system may additionally affect access to care for patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical access and the ability to navigate the complex healthcare system may additionally affect access to care for patients with cancer. People of lower socioeconomic status suffer from disparities in access to high‐quality care from a constellation of intricately linked factors, with known independently associated factors including a person's race, insurance, and education level 2,4‐8 . Identification of additional mechanisms for these disparities could allow for targeted interventions to improve access to care and mitigate disparities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation